2020
DOI: 10.18632/aging.103106
|View full text |Cite
|
Sign up to set email alerts
|

miR-378a-3p inhibits ischemia/reperfusion-induced apoptosis in H9C2 cardiomyocytes by targeting TRIM55 via the DUSP1-JNK1/2 signaling pathway

Abstract: MicroRNAs (miRNAs) are involved in many pathological and biological processes, such as ischemia/reperfusion (I/R) injury by modulating gene expression. Increasing evidence indicates that miR-378a-3p might provide a potential cardioprotective effect against ischemic heart disease. Cell apoptosis is a crucial mechanism in I/R injury. As such, this study evaluated the protective effects and underlying mechanisms of action of miR-378a-3p on H9C2 cardiomyocyte apoptosis following I/R injury. We found that I/R-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Two studies have found that miR-378a-3p promotes the apoptosis of ovarian cancer cells and retinoblastoma cells [ 17 , 23 ]. However, one study demonstrated that miR-378a-3p prevents H9C2 cardiomyocyte cells apoptosis during ischemic injury [ 24 ]. Furthermore, another study reported that miR-378a-3p induces Ferroptosis in rat ischemic kidney injury [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have found that miR-378a-3p promotes the apoptosis of ovarian cancer cells and retinoblastoma cells [ 17 , 23 ]. However, one study demonstrated that miR-378a-3p prevents H9C2 cardiomyocyte cells apoptosis during ischemic injury [ 24 ]. Furthermore, another study reported that miR-378a-3p induces Ferroptosis in rat ischemic kidney injury [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of miR-342-3p in circulating miRNAs in heart failure model mice was significantly reduced ( Kaneko et al, 2017 ). MiR-378a-3p could prevent myocardial apoptosis induced by ischemia-reperfusion injury through TRIM55/DUSP1/JNK signaling ( Tan et al, 2020 ). These proven miRNAs might provide therapeutic targets for myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TRIM35 exerts both oncogenic and tumor suppressor roles in diverse types of tumors and its role in KIRC requires further exploration. Abundant TRIM55 is expressed in cardiac and skeletal muscles and plays significant roles in cardiomyocyte hypertrophy and apoptosis ( 50 , 51 ). The forced expression of TRIM55 inhibits hepatocellular carcinoma cell migration and invasion by reversing the epithelial to mesenchymal transition ( 52 ).…”
Section: Discussionmentioning
confidence: 99%